2002
DOI: 10.1128/jb.184.7.1832-1842.2002
|View full text |Cite
|
Sign up to set email alerts
|

tRNA Is the Source of Low-Level trans- Zeatin Production in Methylobacterium spp

Abstract: Pink-pigmented facultatively methylotrophic bacteria (PPFMs), classified as Methylobacterium spp., are persistent colonizers of plant leaf surfaces. Reports of PPFM-plant dialogue led us to examine cytokinin production by PPFMs. Using immunoaffinity and high-performance liquid chromatography (HPLC) purification, we obtained 22 to 111 ng of trans-zeatin per liter from culture filtrates of four PPFM leaf isolates (from Arabidopsis, barley, maize, and soybean) and of a Methylobacterium extorquens type culture ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
106
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 40 publications
2
106
0
4
Order By: Relevance
“…Methylobacterium, as plant symbionts, utilize the methanol emitted from plants and in turn, impart beneficial effects on plant growth through one or more mechanisms that include production of phytohormones like indoleacetic acid or cytokinins and vitamins (Basile et al, 1985;Koenig et al, 2002;Trotsenko et al, 2001), synthesis of enzymes such as urease or 1-aminocyclopropane-1-carboxylate deaminase (ACCD) that modulate plant growth (Holland and Polacco, 1992;Madhaiyan et al, 2006Madhaiyan et al, , 2007 and production of siderophores (Idris et al, 2004). Monier and Lindow (2003) reported that on different plant species, large aggregates of bacteria are embedded in extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Methylobacterium, as plant symbionts, utilize the methanol emitted from plants and in turn, impart beneficial effects on plant growth through one or more mechanisms that include production of phytohormones like indoleacetic acid or cytokinins and vitamins (Basile et al, 1985;Koenig et al, 2002;Trotsenko et al, 2001), synthesis of enzymes such as urease or 1-aminocyclopropane-1-carboxylate deaminase (ACCD) that modulate plant growth (Holland and Polacco, 1992;Madhaiyan et al, 2006Madhaiyan et al, , 2007 and production of siderophores (Idris et al, 2004). Monier and Lindow (2003) reported that on different plant species, large aggregates of bacteria are embedded in extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Madhaiyan et al, (2004) observed higher photosynthetic activity in rice cultivar Co-47 that received Methylobacterium and attributed the effect due to enhancement of chlorophyll concentration, maleic acid content and increased number of stomata. Using a variety of biochemical and cytological methods, it has been shown that microbes of the genus Methylobacterium produced cytokinin (Koenig et al, 2002). The "classical" phytohormone auxin is also produced and secreted by different strains of Methylobacterium (Hornschuh et al, 2002).…”
Section: Impact Of Ppfm and Pgrs On Spad And Soluble Protein Contentmentioning
confidence: 99%
“…Therefore, it is possible that iP and cZ are produced when modified tRNAs are degraded. In bacteria, modified tRNAs are a source of low-level cytokinin production (31,32); however, there is no experimental evidence for a tRNA-degradation route for cZ production in plants. tRNA IPTs catalyze isopentenylation of certain tRNAs in diverse organisms ranging from bacteria to animals and plants (33), including Arabidopsis (34).…”
mentioning
confidence: 99%